Effects of auditory integrationtraining and acoupedic therapy on word recognition of children with hearing impairment (2017)
This study examined the effectiveness of auditory integration training and acoupedic therapy on word recognition among children with hearing impairment. Thirty three children between five and ten years old participated in this study. All the participants had Pre-Lingual and Post-Lingual hearing impairment with degree of hearing loss ranging from mild, moderate, severe to profound. All the children had their hearing loss confirmed through audiometric test and they were fitted with hearing aids. The instruments used consisted of Macro 53 brand of audiometer calibrated on ISO-13485:2008, word recognition test adapted from Betts (1946) with reliability of 0.89 for pre and post tests and case history of the participants. Data collected were coded and analysed using Analysis of Co-variance using SPSS version 17. The results revealed that Auditory Integration Training and Acoupedic therapy had significant effects on word recognition among the participants and that Auditory Integration Training was more effective on word recognition among children with hearing impairment. Also, there were significant main effects of degree and onset of hearing loss on participants’ word recognition. It was recommended that early intervention in the form of Auditory Integration Training and Acoupedic Therapy should be adopted.